2014
DOI: 10.1063/1.4870236
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the optical properties of nanostructured silicon surfaces for solar cell applications

Abstract: Surface nanostructuration is an important challenge for the optimization of light trapping in solar cell. We present simulations on both the optical properties and the efficiency of micro pillars-MPs-or nanocones-NCs-silicon based solar cells together with measurements on their associated optical absorption. We address the simulation using the Finite Difference Time Domain method, well-adapted to deal with a periodic set of nanostructures. We study the effect of the period, the bottom diameter, the top diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…For example, nano-texturing of the front-side and/or back-side surfaces of the solar cell allows to enhance the coupling of the incident light into the active layer via light trapping [7,8]. Attention is paid to the optimization of this type of texture and a lot of simulations and experimental results on nanostructured solar cells have been published in the last few years [9][10][11][12][13]. In spite of all these efforts, an important question has not yet found a definite answer: Is the best type of corrugation periodic, quasi-periodic or random?…”
Section: Introductionmentioning
confidence: 99%
“…For example, nano-texturing of the front-side and/or back-side surfaces of the solar cell allows to enhance the coupling of the incident light into the active layer via light trapping [7,8]. Attention is paid to the optimization of this type of texture and a lot of simulations and experimental results on nanostructured solar cells have been published in the last few years [9][10][11][12][13]. In spite of all these efforts, an important question has not yet found a definite answer: Is the best type of corrugation periodic, quasi-periodic or random?…”
Section: Introductionmentioning
confidence: 99%
“…Recently, absorption improvement in c-Si thin film solar cells by means of photonic management (PM) engineering, such as photonic crystals, 4,5 nano-wires (nano-rods), 6,7 nanopores (nanoholes), 8,9 nanocones (nanodomes), [10][11][12][13][14][15] and inverted nano-pyramids 16 has been theoretically studied. However, all these light-trapping structures inevitably lead to significant increase in the device surface area and introduce surface defects, resulting in elevated carrier loss.…”
mentioning
confidence: 99%
“…[ 17 ] Previous publications, which focus on pillars with diameters of up to a few µm, have shown a positive effect of increased pillar heights on the effi ciency of solar cells. [ 10,18,19 ] Voigt et al have used simulations to predict the most effi cient pillar radius (in the range 62-4000 nm) and height (range 3-384 µm) [ 18 ] and found an optimum value of 2 µm for the pillar diameter with a corresponding height of 96 µm. Another important aspect in the design of the pillar array is the diameter-over-pitch (D/P) ratio.…”
Section: Doi: 101002/aenm201501728mentioning
confidence: 99%
“…Previous studies in the fi eld of photovoltaics have shown large improvement in solar cell performance, such the highest theoretical and experimental effi ciencies for various systems. [19][20][21] The radial junction depth variation in micropillars can be varied by tuning the doping process, and a trend of improved JV characteristics for thinner junctions, down to 50 nm, has been shown in simulations. [ 20 ] A thin junction leads to less recombination, which implies that the outer highly doped shell of a radially doped micropillar should be kept thin, but also should keep its carrier separation functionality.…”
Section: Introductionmentioning
confidence: 97%